STUDENTS’ PERCEPTIONS OF THE NETFLIX APPLICATION TO IMPROVE THEIR SPEAKING SKILLS - Islami, Fajar Nur; Maghfiroh, Ana (English Education Study Program - Artha Wacana Christian University, 2023)
The use of Netflix as a learning medium in improving speaking skills is very common among teenagers. The platform has provided a large selection of movies that appeal to learners. This research determines students' perceptions of using the Netflix app to improve speaking skills. The data was analyzed using descriptive qualitative methodology, and several previous studies were used to support the research results. This study observed students who use the Netflix platform to practice their speaking skills. To get precise information on how the 27 respondents who are students of Universitas Muhammadiyah Ponorogo. According to the study's findings, the majority of participants were happy utilizing Netflix to hone their communication abilities. The platform, the students agreed, improved their speaking abilities. The Netflix episodes and movies can be used by students to improve their speaking abilities by combining auditory and visual components, using subtitles, and participating in post-viewing activities.